Quo Vadis, Haiti? Can the Kenyan peace operation resuscitate a nation in chaos? - Hárs, András (POLARITIES, 2025)
The state of Haiti has seen several peace operations over the last decades, yet it remains one of the most dangerous countries in the region. With a negative record in terms of gun violence and political assassinations, coupled with an ailing economy and egregious healthcare and education system, the international community does not seem able to find an adequate solution to the myriad problems, nor can the state itself remedy the situation on its own. Amid such turmoil, Kenya has volunteered to send a unique police operation to the country which has obtained the legal backing from the United Nations, funding from the United States and support from the Organization of American States as well as CARICOM along with their constituent member states. It is unclear however how a relatively novel and small operation run by a country from another continent can alter local conditions for the better. It is also yet to be seen if and how the operation compares to its previous iterations in Haiti and whether the lessons from the moderate successes and loud failures were learnt.